EVALUASI PELAKSANAAN PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL DI DESA SIONOM HUDON SELATAN KECAMATAN PARLILITAN KABUPATEN HUMBANG HASUNDUTAN - Evi Haryati Saragih (Welfare StatE, 2013)
The existence of traditional remote community is a reality that can not be ignored in Indonesia, including in North Sumatera. Traditional remote community have been living in pathetic life because they are living in remote places that are difficult to reach, geographically. The isolation also caused traditional remote community can not be a part of the development process as well as society at large. Sustainable development is needed for all aspect of their life and sustenance by increasing standard of living and social welfare from the traditional remote community. This research study was held in the village of Sionom Hudon Selatan sub-district Parlilitan Regency Humbang Hasundutan as one of the location of Empowerment Program for Traditional Remote Community which taken by Agency of Social Welfare Province of North Sumatera coordinated with such local Regional Government and related agencies. Research study using descriptive method with qualitative approach. To obtain necessary data, this research study using data collection technique and field study which consists of questionnaire, interview and observation. Based on the result of data analysis, it was found that there was an increase of social welfare for traditional remote community in the village of Sionom Hudon Selatan after implementation of Empowerment Program for Traditional Remote Community. Program evaluation can be seen from the aspect of input, process, output and impact of the program. The planning and implementation stage of the program has been already well, but the follow-up plan for the program has not been maximal so people are no longer focus for the goals of the process and the end goals of the program. Keywords :evaluation, empowerment, traditional remote community